The Financial Supply Chain Management: Conflicting Trends in Russian Banking - Vladimir V. Strelnikov (International Journal of Supply Chain Management, 2020)
Abstract- Financial supply chain is all about the movement of money along the chain. The subject of the study is the main trends in Russian banking development in the context of modern processes of digitalization, financialization, and disintermediation. The purpose of the work is to determine the systemic contradiction in the development trends of domestic banking system. The author used the systematic approach and general scientific methods, statistical and comparative analysis, expert evaluations and generalizations, logical and functional analysis. The results and scientific novelty of the work are presented in the tendency of outstripping nationalization of banking activity, which poses a threat of an increase in the corresponding systemic contradiction in the emerging financial relations. As a conclusion, it is proposed to focus on the active creation of new tools, excluding the transformation of excessive nationalization of banking into an integrated space of new technology platforms, banking and non-banking ecosystems.